Localización de la Antigua Ciudad de Urci y delimitación de la Frontera Interprovincial entre las Provincias Bética y Tarraconense en Tiempos de Tolomeo - Casado Baena, Mateo (Gerión. Revista de Historia Antigua, 2008)
The main purpose of this article is to determine the probable location of the lost city of Urci from written documents by Pomponious Mela, Gaius Plinius Secundus y Claudius Ptolemaeus. The research, based on these sources, indicates that the location of this site could not have been on or around Almeria City, as proposed by some encyclopedias and by several historians, but to the west, on the lower basin of the Almanzora river. The paper also determines the frontier between the Baetica and Tarraconensis provinces in Ptolemy’s time.